Motor control during an active straight leg raise in pain free and chronic pelvic girdle pain subjects - Beales, Darren (Curtin University, 2009)
Aberrant motor control strategies have been identified in chronic pelvic girdle pain (PGP) subjects. It has been proposed that aberrant motor control strategies could provide a mechanism for ongoing pain and disability in these subjects. This thesis consists of a series of studies that have investigated motor control strategies during the active straight leg raise (ASLR) test, under various loading conditions, in pain free nulliparous female subjects (n=14) and female subjects with chronic PGP (n=12). Clinical examination of the chronic PGP subjects had identified the SIJ and surrounding structures as the primary source of symptoms. Heaviness of the leg (+/- pain) when the pain subjects performing the ASLR was relieved in all the pain subjects with the addition of manual pelvic compression during the ASLR, consistent with a pain disorder associated with impaired force closure mechanism.Phase of respiration was monitored with the pneumotach. Electromyography was recorded bilaterally from internal obliquus abdominis (IO), external obliquus abdominis, rectus abdominis, anterior scaleni and rectus femoris as well as the right chest wall (CW). Intra-abdominal pressure (IAP) and intra-thoracic pressure were measured with a nasogastric catheter attached to custom-made pressure transducer equipment. Downward pressure of the non-lifted leg during an ASLR was recorded with an inflated pad linked to a pressure transducer placed under the heel. Data for these variables were collected in a custom designed data acquisition program. A separate custom designed program was used for data processing. Additionally, motion of the pelvic floor (PF) was monitored with a real-time ultrasound unit and recorded to digital video for manual processing.Study 1: Motor control patterns during an active straight leg raise in pain free subjects Pain free subjects demonstrated greater muscle activation of the abdominal and CW ipsilateral to the side the ASLR was performed on. This effect was most pronounced local to the pelvis in IO. This muscle pattern was associated with a small increase in IAP. Although there was an overall commonality in the motor control patterns, individual variation was apparent. This study contradicted the theory of anterior diagonal slings for the provision of pelvic stability/force closure during the ASLR. The findings of this study highlights the flexibility of the neuromuscular system in controlling load transference during an ASLR, and the plastic nature of the abdominal cylinder.Study 2: Motor control patterns during an active straight leg raise in chronic pelvic girdle pain subjects In contrast to pain free subjects, chronic PGP subjects demonstrated bracing of the abdominal wall and right CW during an ASLR on the symptomatic side of the body. This was associated with higher levels of IAP and increased downward movement of the PF. Increased levels of IAP could have negative consequences and be provocative of pain. The findings from this study support the notion that aberrant motor activation patterns exist in this group of subjects.Study 3: The effect of increased physical load during an active straight leg raise in pain free subjects When performing an ASLR with additional physical load around the ankle, pain free subjects demonstrated increased muscle activation levels compared to an ASLR without additional load, with higher levels of IAP. Greater ipsilateral IO activation observed during an ASLR was maintained during the loaded ASLR, unlike the symmetrical bracing pattern observed in PGP subjects. This adds support to the notion that PGP subjects have aberrant motor control patterns during an ASLR, not represented solely by the increased effort of lifting the leg.Study 4: The effect of resisted inspiration during an active straight leg raise in pain free subjects Pain free subjects performed an ASLR while also breathing with inspiratory resistance, to simultaneously provide a stability and respiratory challenge upon the neuromuscular system. Motor activation in the abdominal wall was highlighted by a cumulative increase in motor activation when performing the ASLR with inspiratory resistance compared to performing these tasks in isolation. Despite this general increase in activation, a pattern of greater IO activity on the side of the leg lift observed during an ASLR was preserved when inspiratory resistance was added to the ASLR. Intra-abdominal pressure demonstrated an incremental increase similar to the increase in muscle activity. This confirms that pain free subjects are able to adapt to multiple demands of an ASLR and inspiratory resistance by an accumulative summation of the patterns utilised when these tasks are performed independently.Study 5: Non-uniform motor control changes with manually applied pelvic compression during an active straight leg raise in chronic pelvic girdle pain subjects The PGP subjects performed an ASLR with the addition of manual pelvic compression. The hypothesis that this would reduce muscle activation levels and IAP was not supported. Rather, trends for either trunk muscle facilitation or inhibition were identified. Trunk muscle facilitation was associated with higher levels of IAP, whereas motor inhibition was associated with lower levels of IAP. These findings suggest a potential for different underlying mechanism associated with the chronic PGP disorder in these subjects and variable responses to pelvic compression.While a number of the statistical analyses were significant suggesting some consistency in motor patterns, visual inspection of the data demonstrated individual variations in the motor control strategies in both pain free and chronic PGP subjects.Taken together, these findings demonstrate that: * Pain free subjects adopt a predominant pattern of greater motor activation ipsilateral to the side of the leg lift during an ASLR, an ASLR with additional physical load and an ASLR performed with inspiratory resistance. Within this commonality in motor control, individual variations exist. * Chronic PGP subjects do not demonstrate greater ipsilateral activation during an ASLR on the symptomatic side. Instead they adopt a bilateral bracing/splinting motor control pattern with increased IAP.It is hypothesised that: The aberrant motor control patterns observed in these chronic PGP subjects may be maladaptive in nature. These aberrant patterns may have negative consequences on pelvic loading and stability, respiration, continence, pain and disability. The findings of this thesis are consistent with complex underlying mechanisms driving chronic pelvic girdle pain disorders, and suggest that multiple factors have the potential to influence motor control strategies in these subjects. These findings may have implications for management of chronic PGP disorders, highlighting the need for individualised programs that attempt to normalise aberrant motor control strategies.This thesis has added substantially to the knowledge of motor control in chronic PGP disorders, a research area in its infancy compared to the investigation of motor control in the lumbar and cervical regions of the spine. Now that PGP has been recognised as a separate diagnostic entity to LBP, greater understanding of this region is essential for the identification of sub-groups within the diagnosis of PGP, and for the development of specific intervention strategies that target the underlying pain mechanisms driving these disorders.